Texas Divided : Loyalty and Dissent in the Lone Star State, 1856-1874 - Marten, James Alan (Book collections on Project MUSE., 2009)
Texas, unlike other states of the Confederacy, was virtually untouched by the military campaigns of the Civil War. Moreover, it was home to two considerable ethnic groups Germans and Hispanics who had no traditional ties with the southern way of life. In this book James Marten offers the first general exploration of the shifting relationships among the contending political and ethinic factions in Texas during the sectional crisis of the mid-nineteenth centry.